Preparado para el grupo participantes del Taller de Mustia - Abawi, G.S.; Pastor Corrales, Marcial A. (International Center for Tropical Agriculture, 1987)
The procedures to be followed for the preparation of Rhizoctonia solani inoculum and of inoculum using R. solani micelium, and for the determination of R. solani populations in the soil (complete soil method, OM test, and pathogen attraction) are given. Recommendations for the International Web Blight Nursery include an international evaluation scale from 1 to 9, agronomic management of trials, control strategies (cultural, chemical, integrated), and research goals regarding ecology, biology, epidemiology, moist chamber inoculation, reaction to "cock`s eye", population management, and inheritance studies. (CIAT)